The role of Ephrins-B1 and - B2 during fetal rat lung development - Silva, Cristina Isabel Nogueira (2015)
Background/Aims: The knowledge of the molecular network that governs fetal lung branching is an essential step towards the discovery of novel therapeutic targets against pulmonary pathologies. Lung consists of two highly branched systems: airways and vasculature. Ephrins and its receptors, Eph, have been implicated in cardiovascular development, angiogenesis and vascular remodeling. This study aims to clarify the role of these factors during lung morphogenesis. Methods: Ephrins-B1, -B2 and receptor EphB4 expression pattern was assessed in fetal rat lungs between 15.5 and 21.5 days post-conception, by immunohistochemistry. Fetal rat lungs were harvested at 13.5 dpc, cultured during 4 days and treated with increasing doses of ephrins-B1 and -B2 and the activity of key signaling pathways was assessed. Results: Ephrin-B1 presents mesenchymal expression, whereas ephrin-B2 and its receptor EphB4 were expressed by the epithelium. Both ephrins stimulated pulmonary branching. Moreover, while ephrin-B1 did not affect the pathways studied, ephrin-B2 supplementation decreased activity of JNK, ERK and STAT. This study characterizes the expression pattern of ephrins-B1, -B2 and EphB4 receptor throughout rat lung development. Conclusion: Our data highlight a possible role of ephrins as molecular stimulators of lung morphogenesis. Moreover, it supports the idea that classical vascular factors might play a role as airway growth promoters.